2021
DOI: 10.3390/cancers13184711
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Radiotherapy vs. Localized Radiotherapy after Resection of Brain Metastases in the Era of Targeted Therapy: A Retrospective Study

Abstract: Whether targeted therapy (TT) and radiotherapy impact survival after resection of brain metastases (BM) is unknown. The purpose of this study was to analyze the factors affecting overall survival (OS), local control (LC), distant control (DC), and leptomeningeal metastases (LMM) in patients who had undergone resection of BM. We retrospectively analyzed 124 consecutive patients who had undergone resection of BM between 2004 and 2020. Patient information about age, sex, Karnofsky Performance Scale (KPS), origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
2
2
Order By: Relevance
“…However, in the subgroup of patients who received either targeted therapy or chemotherapy, we found that WBRT did not demonstrate survival benefits, which is consistent with the result of a meta-analysis that found no OS benefit with the addition of targeted therapy to radiotherapy ( 31 ). However, despite previous studies demonstrating that the KPS score is associated with survival outcomes ( 27 , 32 ), we did not observe this in the present study, which might attributable to the high overall KPS scores of our patients. Combining the beneficial features of high KPS, controlled primary disease, and single BM, it is not surprising that the median OS in this patient cohort was 27.1 months, which was longer than that reported previously (11.6–21.1 months) ( 10 , 22 , 27 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in the subgroup of patients who received either targeted therapy or chemotherapy, we found that WBRT did not demonstrate survival benefits, which is consistent with the result of a meta-analysis that found no OS benefit with the addition of targeted therapy to radiotherapy ( 31 ). However, despite previous studies demonstrating that the KPS score is associated with survival outcomes ( 27 , 32 ), we did not observe this in the present study, which might attributable to the high overall KPS scores of our patients. Combining the beneficial features of high KPS, controlled primary disease, and single BM, it is not surprising that the median OS in this patient cohort was 27.1 months, which was longer than that reported previously (11.6–21.1 months) ( 10 , 22 , 27 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, despite previous studies demonstrating that the KPS score is associated with survival outcomes ( 27 , 32 ), we did not observe this in the present study, which might attributable to the high overall KPS scores of our patients. Combining the beneficial features of high KPS, controlled primary disease, and single BM, it is not surprising that the median OS in this patient cohort was 27.1 months, which was longer than that reported previously (11.6–21.1 months) ( 10 , 22 , 27 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At the same manner, immune checkpoint inhibitors (ICI) anti PD-1/PDL-1 (nivolumab, pembrolizumab, atezolizumab, durvalumab) and anti-CTLA-4 inhibitors (Ipilimumab, tremelimumab) are increasingly used for treating patients with advanced disease [12][13][14], whilst combining targeted-and immune-based therapies is being evaluated in a variety of solid tumors [15]. Notably, accordingly to the ability of these drug to penetrate the blood-brain barriers, targeted-and immune-based therapies, alone or in combination, have shown a therapeutic e ciency in treating BM [5][6][7][8], whilst increasing evidence suggest their use in combination with radiotherapy (RT) [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%